Limit of detection of genomic DNA by conventional PCR for estimating the load of Staphylococcus aureus and Escherichia coli associated with bovine mastitis - Chandrashekhar, K M; Isloor, Shrikrishna; Veeresh, B H; Hegde, Raveendra; Rathnamma, D; Murag, Shivaraj; Veeregowda, B M; Upendra, H A; Hegde, Nagendra R (Folia microbiologica, 2015)
Detection of mastitis-associated bacteria can be accomplished by culturing or by molecular techniques. On the other hand, rapid and inexpensive methods to enumerate bacterial load without culturing can be better achieved by molecular methods. Staphylococcus aureus and Escherichia coli are the predominant bacterial pathogens associated with bovine mastitis. Here, we describe the application of conventional PCR for the limit of detection (LOD) of genomic DNA of S. aureus and E. coli based on single-copy genes. The selected genes were thermonuclease (nuc), aureolysin (aur), and staphopain A (scpA) for S. aureus and β-D-glucuronidase A (uidA), cytochrome d oxidase (cyd), and rodA (a gene affecting cell shape and methicillin sensitivity) for E. coli. The LOD was 5.3, 15.9, and 143 pg for aur, nuc, and scpA genes, corresponding to S. aureus genomic copies of 1.75 × 10(3), 5.16 × 10(3), and 4.71 × 10(4), respectively. The LOD was 0.45, 12.3 and 109 pg for uidA, rodA and cyd genes, corresponding to E. coli genome copies of 8.91 × 10(1), 2.43 × 10(3), and 2.16 × 10(4), respectively. Application of uidA and aur PCRs to field strains revealed that as low as approximately 100 genome copies of E. coli and 1000-10,000 copies of S. aureus could be detected. This study is the first to report LOD of genomic DNA using conventional PCR for aur and scpA genes of S. aureus, and rodA and cyd genes of E. coli. The results should be useful for developing assays to assess bacterial load in milk and to determine the load that contributes to subclinical or clinical mastitis.
Keywords: Staphylococcal Infections; infekce vyvolané Escherichia coli; Limit of Detection; Staphylococcus aureus; Escherichia coli Infections; limita detekce; DNA bakterií; stafylokokové infekce; Female; Escherichia coli; zvířata; bakteriální proteiny; Mastitis, Bovine; DNA, Bacterial; Cattle; ženské pohlaví; polymerázová řetězová reakce; skot; Polymerase Chain Reaction; Bacterial Proteins; mastitida skotu; Animals